A kiváló csapat főbb jellemzői - Gulyás, László; Turcsányi, Enikő (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Nowadays the "team", "team-works" "team-player" and "team-buildings" are the very important area of management studies. Our paper examines small pieces of this area, we examine the features of excellent team. One author of this paper is psychologist, the other one is HR-manager, both of them investigate the features of excellent team from their point of view.